Etika dan Tantangan Dakwah di Era Kecerdasan Buatan - Insana, Zuharin; Satriah, Lilis (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2024)
This study examines the use of artificial intelligence (AI) chatbots in religious consultations, particularly in the context of Islamic preaching (dawah). The aim of the research is to evaluate the benefits and challenges faced in the implementation of this technology and to identify the ethical approaches needed for its development and use. The research methods include literature analysis and case studies. The results indicate that AI chatbots can enhance accessibility and efficiency in providing religious guidance but also raise several ethical and theological issues. With the right ethical approach, AI chatbots have great potential to support dawah in the digital age.